Game of thrones : a guide to Westeros and beyond : the complete series - McNutt, Myles (London : Michael Joseph, 2019)
As the world waits in anticipation for the final series of the biggest TV show in history, Game of Thrones, this book takes viewers deeper into the world of Westeros than ever before. Packed with insightful essays and illustrated with detailed timelines, maps, infographics and photography, this is the ultimate companion for every fan. Exploring the complex stories, characters, relationships, and world-building, this book covers everything from Seasons 1 to 8.
Keywords: fantasiasarjat; televisiosarjat; fiktiiviset hahmot; fiktiiviset paikat; oppaat (teokset)